Harvesting history : McCormick's reaper, heritage branding, and historical forgery - Ott, Daniel P. (University of Nebraska Press, 2023)
"Harvesting History explores how the highly contentious claim of Cyrus McCormick's 1831 invention of the reaper came to be incorporated into the American historical canon as a fact. Spanning the late 1870s to the 1930s, Daniel P. Ott reveals how the McCormick family and various affiliated businesses created a usable past about their departed patriarch, Cyrus McCormick, and his role in creating modern civilization through advertising and the emerging historical profession. The mythical invention narrative was widely peddled for decades by salesmen and in catalogs, as well as in corporate public education campaigns and eventually in history books, to justify the family's elite position in American society and its monopolistic control of the harvester industry in the face of political and popular antagonism. As a parallel story to the McCormicks' manipulation of the past, Harvesting History also provides a glimpse of the nascent discipline of history during the Progressive Era. Early historians were anxious to demonstrate their value in the new corporate economy as modern professionals and "objective" guardians of the past. While ethics might have prevented them from being historians for hire, their own desire for inclusion in the emerging middle class predisposed them to be receptive to both the McCormicks' financial influence as well as their historical messages. "--